1995
DOI: 10.1007/bf02541031
|View full text |Cite
|
Sign up to set email alerts
|

Role of alkanols in micellar growth: A viscometric study

Abstract: We have measured the viscosity of solutions of 0.3 M sodium dodecy[ sulfate (SDS) + 0.3 M NaBr + n-alkanols as a function of [alkanol] and temperature. When propanol was added, the viscosity of micellar solutions remained almost constant and then decreased, whereas it continuously increased with hexanol. However, with butanol or pentanol, depending upon the added concentration, increases followed by decreases in viscosity were observed. This behavior has been discussed in light of solubility of alkanols in var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Self association of surfactant molecules into spherical micelles becomes apparent around the critical micelle concentration (cmc) . The spherical micelles show unidimensional (the so-called rod-shaped micelles) growth in certain systems on increasing the surfactant concentration and/or depending upon appropriate conditions of salinity, temperature, and presence of suitable additives (salt, alcohol, amine, ,− or hydrocarbon 21,32-38 ). Here micellar growth is achieved by forming rodlike micelles of increasing length.…”
Section: Introductionmentioning
confidence: 99%
“…Self association of surfactant molecules into spherical micelles becomes apparent around the critical micelle concentration (cmc) . The spherical micelles show unidimensional (the so-called rod-shaped micelles) growth in certain systems on increasing the surfactant concentration and/or depending upon appropriate conditions of salinity, temperature, and presence of suitable additives (salt, alcohol, amine, ,− or hydrocarbon 21,32-38 ). Here micellar growth is achieved by forming rodlike micelles of increasing length.…”
Section: Introductionmentioning
confidence: 99%
“…We are engaged in a systematic study of effects of addition of salts and organic molecules singly/jointly on micellar growth in aqueous ionic surfactant solutions. Our investigations have primarily been concerned with how viscosity measurements can be used to study the micellar growth/shape transition and how the combined presence of salt−organics influences the viscosity and overall organization of surfactant molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants with smaller a tend to form larger, less curved, or even inverted aggregates. For ionic surfactants, the area shrinking effect may be obtained by salt (with common counter-ion) addition (13,14) or organic compound solubilization (6,7,(15)(16)(17).…”
mentioning
confidence: 99%
“…More studies are needed to increase understanding of the effect of hydrocarbons on the properties of micellar systems and micellar growth. In the last few years, the authors have reported micellar growth processes in the presence of various alcohols and amines (7,(15)(16)(17). These reports have shown how these compounds can be used to vary the area per ionic group (a), a parameter of overriding importance for such growth processes.…”
mentioning
confidence: 99%